2020
DOI: 10.1111/jerd.12568
|View full text |Cite
|
Sign up to set email alerts
|

Three‐year clinical performance of monolithic and partially veneered zirconia ceramic fixed partial dentures

Abstract: Objective: To compare the 3-year survival and success rates of monolithic (M) and partially veneered (PV) zirconia-fixed partial dentures (FPDs). Materials and Methods:Sixty-seven FPDs (n = 33 M-FPDs; n = 34 PV-FPDs) were placed in 51 patients (n = 23 males; mean age 61.5 years) and clinically followed up 1 week, 6 months, and then yearly after placement. One hundred per cent (100%) of M-FPDs and 70% of PV-FPDs were located in the posterior region. Ninety-two per cent (92%) of M-FPDs had three units, whereas 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 34 publications
2
19
0
2
Order By: Relevance
“…The studies mainly focused on tooth‐supported posterior crowns, reporting survival rates at 1 to 3.5 years follow‐up in the range of 91.5% to 100%, 35,36,51,53,55–57 and one study reported a survival rate of 76.9% that could be due to the inclusion of patients with bruxism and because monolithic zirconia restorations are stiff and unable to absorb stresses 54 . Nevertheless, studies on posterior second‐generation monolithic zirconia FPDs are scarce, reporting a survival rate ranging from 96.7% to 100%, and consistent with the findings of the study 54,58,59 …”
Section: Discussionmentioning
confidence: 96%
“…The studies mainly focused on tooth‐supported posterior crowns, reporting survival rates at 1 to 3.5 years follow‐up in the range of 91.5% to 100%, 35,36,51,53,55–57 and one study reported a survival rate of 76.9% that could be due to the inclusion of patients with bruxism and because monolithic zirconia restorations are stiff and unable to absorb stresses 54 . Nevertheless, studies on posterior second‐generation monolithic zirconia FPDs are scarce, reporting a survival rate ranging from 96.7% to 100%, and consistent with the findings of the study 54,58,59 …”
Section: Discussionmentioning
confidence: 96%
“…One problem identified in the study is the opacity of the monolithic material, which led to a reduction in the FDI scores for “color match and translucency.” Clinically good values were nonetheless still achieved, and top scores for the criterion “patient's view of esthetics” suggest that this probably did not affect patient acceptance. This is also suggested by studies on monolithic zirconia single crowns and FPDs, in which patients usually awarded top scores for restoration appearance, whereas dentists were more critical of the esthetic outcome 38,39 …”
Section: Discussionmentioning
confidence: 83%
“…The continual development of zirconia RBFPDs toward a fully monolithic design is likely to further improve the prognosis of this type of restoration 27 . Not only does this design have the potential to eliminate chipping problems, 38,39 but it also enables the application of delicate preparation geometries and thus the use of retentively prepared adhesive wings as anchoring elements, as an alternative to inlays.…”
mentioning
confidence: 99%
“…and reduced cost and time for the production compared with porcelain-fused-tozirconia [8]. Although the monolithic approach is not new, monolithic Y-TZP posterior restorations have a signi cant advantage due to their high fracture resistance [9,10].…”
Section: Introductionmentioning
confidence: 99%